Norway and the polar regions - Hansson, Rasmus (The Royal Norwegian Ministry of Foreign Affairs, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Norge og polarområdene - Hansson, Rasmus (ed.) (Utenriksdepartementet, 1998)
Keywords: Antarktis; Norge; geografi; historie; miljøvern; polarforskning; polarområdene; politikk

Large spatial variation in accumulation rate in Jutulstraumen ice stream, Dronning Maud Land, Antarctica - Melvold, Kjetil; Hagen, Jon Ove; Pinglot, Jean Francis; Gunuestrup, Niels (Annals of Glaciology, 1998)
A mass-balance programme was initiated on Jutulstraumen ice stream, western Dronning Maud Land,Antarctica, during the austral summer 1992-93. As a part of the mass-balance programme, accumulation rate was measured along the centre line of Jutulstraumen from the shelf edge up to the plateau at about 2500 m a.s.l. Accumulation distribution obtained from seven shallow firn cores and 48 slake readings is presented. The overall net accumulation trend displays a decreasing accumulation with increasing elevation and distance to coast, but on both the mesoscale and microscale there are significant variations. This is due to complex patterns of precipitation controlled by orography and redistribution by katabatic winds. The local accumulation distribution (few km scale) was found to be dependent on downslope surface gradient (aspect north, northwest), and variations up to 100% were found over distances of less than 3 km. The large variation in accumulation is important when selecting new core sites and for interpretation of temporal and spatial variations in accumulation derived from firn cores.
Keywords: Dronning Maud Land; geofysikk; geografi; glasiologi; isstrøm

Kvitkuven: Kronprinsesse Märtha Kyst (Norsk Polarinstitutt, 1997)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Vestfjella Aust: Maudheimvidda (Norsk Polarinstitutt, 1997)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Vestfjella Vest: Maudheimvidda (Norsk Polarinstitutt, 1997)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Ahlmannryggen: Maudheimvidda (Norsk Polarinstitutt, 1996)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Jutulstraumen: Maudheimvidda (Norsk Polarinstitutt, 1996)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Using multiple data sources to enhance photogrammetry for mapping Antarctic terrain - Fox, Adrian J (Polar Research, 1995)
Keywords: Antarktis; flyfoto; geografi; kartlegging; luftfoto; satellittbilder

Geographical discoveries in Antarctica by the whaling industry - Headland, Robert Keith (Whaling and history : perspectives on the evolution of the industry, 1993)
Keywords: Antarktis; Carl Anton Larsen; Lars Christensen; ekspedisjoner; geografi; hvalfangst; oppdagelsesreiser

Nature environment map: Gjelsvikfjella and Western Mühlig-Hofmannfjella, Dronning Maud Land, Antarctica - Høgvard, K (Norsk Polarinstitutt, 1993)
Keywords: Dronning Maud Land; NARE 1984/85; NARE 1989/90; geografi; kartlegging

Jutulsessen: Fimbulheimen (Norsk Polarinstitutt, 1992)
Keywords: Dronning Maud Land; Troll forskningsstasjon; geografi; kartlegging; satellite bilder

H.U. Sverdrupfjella: Fimbulheimen (Norsk Polarinstitutt, 1991)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Jutulgryta: Fimbulheimen (Norsk Polarinstitutt, 1991)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Mühlig-Hofmannfjella Nord: Fimbulheimen (Norsk Polarinstitutt, 1991)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Mühlig-Hofmannfjella Sør: Fimbulheimen (Norsk Polarinstitutt, 1991)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Heimfrontfjella Nord: Maudheimvidda (Norsk Polarinstitutt, 1988)
Keywords: Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Heimfrontfjella Sør: Maudheimvidda (Norsk Polarinstitutt, 1988)
Keywords: Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Namnemanus Peter I Øy (Norsk Polarinstitutt, 1988)
Keywords: Peter I. Øy; geografi; kartlegging

Norway's polar territories - Barr, Susan (Aschehoug, 1987)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Peter I. Øy; geografi; geologi; historie; polarområdene; polarpolitikk

Flichnerfjella Nord: Fimbulheimen (Norsk Polarinstitutt, 1984)
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Norge i polarområdene - Egeland, Knut (Leif Holtedahls forl., 1982)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Forposten: Fimbulheimen (Norsk Polarinstitutt, 1975)
Keywords: Den norske antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Sarkofagen: Fimbulheimen (Norsk Polarinstitutt, 1975)
Keywords: Den norske antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Schirmacheroasen: Fimbulheimen / Prinsesse Astrid Kyst (Norsk Polarinstitutt, 1973)
Keywords: Den norske antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Starheimtind: Fimbulheimen / Prinsesse Astrid Kyst (Norsk Polarinstitutt, 1973)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Annandagstoppane. Maudheimvidda (Norsk Polarinstitutt, 1972)
Keywords: Dronning Maud Land; geografi; kartlegging

Vestfjella Aust: Maudheimvidda (Norsk Polarinstitutt, 1972)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk Antarktisekspedisjon 1968-69; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Vestfjella Vest: Maudheimvidda (Norsk Polarinstitutt, 1972)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk Antarktisekspedisjon 1968-69; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Humboldtfjella: Fimbulheimen (Norsk Polarinstitutt, 1968)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Wohlthatmassivet: Fimbulheimen (Norsk Polarinstitutt, 1968)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Erobringen av Antarktis - Harstad, Herlof (Aschehoug, 1968)
Keywords: Antarktis; Sydpolen; biografier; ekspedisjoner; geografi; historie; oppdagelsesreiser; polarekspedisjoner

Filchnerfjella Nord: Fimbulheimen (Norsk Polarinstitutt, 1966)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Mühlig-Hofmannfjella Nord: Fimbulheimen (Norsk Polarinstitutt, 1966)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Glopeflya: Fimbulheimen (Norsk Polarinstitutt, 1964)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Hoelfjella Sør: Fimbulheimen (Norsk Polarinstitutt, 1964)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Sydishavet og tilgrensende områder: Blad 11 - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1964)
Keywords: Norsel (skip); Sørishavet; geografi; kartlegging

Kronprinsesse Märtha Kyst - Maudheimvidda: Dronning Maud Land (Norsk Polarinstitutt, 1963)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Maudheimvidda Aust: Dronning Maud Land (Norsk Polarinstitutt, 1963)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

In Amundsen's Tracks on the Axel Heiberg Glacier - Herbert, Walter William (The Geographical Journal, 1963)
Keywords: Antarktis; Roald Amundsen; ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Borgmassivet: Maudheimvidda (Norsk Polarinstitutt, 1962)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Filchnerfjella Sør: Fimbulheimen (Norsk Polarinstitutt, 1962)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Giæverryggen: Maudheimvidda (Norsk Polarinstitutt, 1962)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Mühlig-Hofmannfjella Sör: Fimbulheimen (Norsk Polarinstitutt, 1962)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; flyfoto; geografi; kartlegging; luftfoto

Ahlmannryggen: Fimbulheimen (Norsk Polarinstitutt, 1961)
Keywords: Den norske antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

H.U.Sverdrupfjella: Fimbulheimen (Norsk Polarinstitutt, 1961)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Jutulgryta: Fimbulheimen (Norsk Polarinstitutt, 1961)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Jutulgryta: Fimbulheimen (Norsk Polarinstitutt, 1961)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Jutulstraumen: Maudheimvidda (Norsk Polarinstitutt, 1961)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Kirwanveggen: Maudheimvidda (Norsk Polarinstitutt, 1961)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; geografi; kartlegging

Neumayerskarvet: Maudheimvidda (Norsk Polarinstitutt, 1961)
Keywords: Den Norske Antarktisekspedisjonen 1956-60; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; flyfoto; geografi; kartlegging; luftfoto

Dronning Maud Land: Sør-Rondane - Luncke, Bernhard (Norsk Polarinstitutt, 1957)
Keywords: Antarktiske ekspedisjon 1946-47; Dronning Maud Land; Richard Evelyn Byrd; flyfoto; geografi; kartlegging; luftfoto

Femti år for Kongen - Riiser-Larsen, Hjalmar (Gyldendal, 1957)
Keywords: Antarktis; Hjalmar Riiser; Larsen; biografier; ekspedisjoner; geografi; kartlegging; luftfart; oppdagelsesreiser; polarforskning; polarområdene

Air operations of the Norwegian-British-Swedish Antarctic Expedition in 1952 - Essen, Reinhold von (Polar Record, 1956)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; flyfoto; forskning; geografi; luftfoto

Harpuner og mannfolk : fra en fangstferd i Antarktis - Ree, Ørnulf (A.S Sæbbøs, 1953)
Keywords: Sørishavet; geografi; historie; hvalfangere; hvalfangst

Maudheim : to år i Antarktis : den norsk-britisk-svenske vitenskapelige ekspedisjon til Antarktis 1949-1952 - Giæver, John (Gyldendal, 1952)
Keywords: Dronning Maud Land; Maudheim (Antarktis); ekspedisjoner; forskning; forskningsstasjoner; geografi; historie; oppdagelsesreiser; overvintring; sjøreiser

A Radar Survey of the Ice Barrier - Higgins, Robert (Journal of Navigation, 1952)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning; geografi; geologi

Sydishavet: Blad 2 - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1950)
Keywords: Bouvetøya; Dronning Maud Land; Sørishavet; geografi; kartlegging

Sydishavet og tilgrensende farvann: Blad 12 - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1949)
Keywords: Sørishavet; geografi; hvalfangst; kartlegging

Antarktis - Luncke, Bernhard (Norges Svalbard- og ishavs-undersøkelsers kartarbeider og anvendelsen av skrå-fotogrammer tatt fra fly, 1949)
Keywords: Antarktis; geografi; kartlegging

Antarktis/Antarctica: Kart nummer 7 - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1946)
Keywords: Antarktis; Lars Christensen; ekspedisjoner; flyfoto; geografi; kartlegging; luftfoto

Sydishavet (Blad 5) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1946)
Keywords: Sørishavet; geografi; kartlegging

Sydishavet (Blad 7) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1946)
Keywords: Sørishavet; geografi; kartlegging

Sydishavet (Blad 8) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1946)
Keywords: Sørishavet; geografi; kartlegging

Roald Amundsens opdagelsesreiser - Amundsen, Roald (Gyldendal, 1942)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; geografi; historie; oppdagelsesreiser

Bouvet-Insel - Engelmann, Gerhard (Geographische Zeitschrift, 1940)
Keywords: Bouvetøya; geografi; historie

Det Norske Geografiske Selskap (The Geographical Journal, 1939)
Keywords: Antarktis; Det Norske Geografiske Selskap; ekspedisjoner; geografi; polarområdene

Recent Reconnaissance Flights in the Antarctic - Christensen, Lars (The Geographical Journal, 1939)
Keywords: Antarktis; Lars Christensen; Thorshavn ekspedisjon; flyfoto; geografi; hvalfangere; hvalfangst; luftfoto; oppdagelsesreiser

The Course of Antarctic Exploration between Longitudes 20° W. and 110° E. Notes on the map compiled to accompany the paper by Mr. Lars Christensen - Christensen, Lars (The Geographical Journal, 1939)
Keywords: Antarktis; Lars Christensen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; oppdagelsesreiser

Min siste ekspedisjon til Antarktis 1936-1937: med en oversikt over forskningsarbeidene på ferdene 1927-1937 - Christensen, Lars (Tanum, 1938)
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjoner; Odd I; Sydpolen; Thorshavn ekspedisjoner; geografi; hvalfangere; hvalfangst

Sydishavet - Balleny öyene (Blad 3) (Hvalfangernes Assuranceforening, 1937)
Keywords: Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Sydishavet - Hearst Land, Charcot ö (Blad 4) (Hvalfangernes Assuranceforening, 1937)
Keywords: Norvegia ekspedisjoner; Peter I. Øy; Sørishavet; geografi; kartlegging

Sydishavet - Kong Haakon VII Hav (Blad 1) (Hvalfangernes Assuranceforening, 1937)
Keywords: Bouvetøya; Norvegia ekspedisjonene; Sørishavet; Thorshammer ekspedisjon; geografi; kartlegging

Sydishavet - Kronprins Olav Land (Blad 2) (Hvalfangernes Assuranceforening, 1937)
Keywords: Lars Christensen; Norvegia ekspedisjonene; Sørishavet; Thorshavn ekspedisjon; geografi; kartlegging

Sydishavet (Blad 6) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1937)
Keywords: Sørishavet; geografi; kartlegging

Sydishavet (Blad 7) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1937)
Keywords: Sørishavet; geografi; kartlegging

Sydishavet (Blad 8) - Hansen, Hans Edvard (Hvalfangernes Assuranceforening, 1937)
Keywords: Sørishavet; geografi; kartlegging

Antarktis og Sydishavet (Norwegian Mapping Authority / Kartverket, 1936)
Keywords: Antarktis; Jason ekspedisjonene; Norvegia ekspedisjoner; Odd I; Sørishavet; Thorshavn ekspedisjon; ekspedisjonen; geografi; kartlegging

Sydishavet (Blad 1) (Hvalfangernes Assuranceforening, 1936)
Keywords: Bouvetøya; Norvegia ekspedisjonene; Sørishavet; geografi; kartlegging

Tilsjøs under napoleonskrigene : en norsk sjømanns opplevelser 1802-1854 - Eide, Henrik O (Aschehoug, 1936)
Keywords: Sørishavet; biografi; ekspedisjoner; fangst; geografi; historie; sjøfolk; skippere

Modifications des Noms de lieu du Continent Antarctique - Hansen, Hans Edvard (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1936)
Keywords: Antarktis; Lars Christensen; Thorshavn ekspedisjon; flyfoto; geografi; kartografi; luftfoto; oppdagelsesreiser

Bunnen av Weddellhavet (Hvalfangernes Assuranceforening, 1935)
Keywords: Bouvetøya; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Sydishavet (Blad 2) (Hvalfangernes Assuranceforening, 1935)
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjoner; Sørishavet; Thorshavn ekspedisjon; geografi; kartlegging

Sydishavet - Weddel Havet - Kong Haakon VII hav (Blad 1) (Hvalfangernes Assuranceforening, 1935)
Keywords: Bouvetøya; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Opdagelsen Av Ingrid Christensen Land - Mikkelsen, Klarius (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1935)
Keywords: Antarktis; Ingrid Christensen Land; Thorshavn ekspedisjon; geografi; kartlegging; kartografi; oppdagelsesreiser

Norvegia rundt sydpollandet : Norvegia-ekspedisjonen 1930-1931 - Isachsen, Gunnar (Gyldendal, 1934)
Keywords: Antarktis; Hjalmar Riiser; Lars Christensen; Larsen; Norvegia ekspedisjonen; Sydpolen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; meteorologi; oppdagelsesreiser; oseanografi

Sydishavet (Blad 2) (Hvalfangernes Assuranceforening, 1933)
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Sydishavet (Blad 3) (Hvalfangernes Assuranceforening, 1933)
Keywords: Antarktis; Sørishavet; ekspedisjoner; geografi; kartlegging

Sydishavet - Weddel Havet - Kong Haakon VII hav (Blad 1) (Hvalfangernes Assuranceforening, 1933)
Keywords: Bouvetøya; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Norwegian Explorations in the Antarctic, 1930-1931 - Isachsen, Gunnar (Geographical Review, 1932)
Keywords: Antarktis; Hjalmar Riiser; Lars Christensen; Larsen; Norvegia ekspedisjoner; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; meteorologi; oppdagelsesreiser; oseanografi

Relation of the Work of the Mawson and Norwegian Antarctic Expeditions, 1930-1931 - Joerg, Wolfgang Louis Gottfried (Geographical Review, 1932)
Keywords: Antarktis; Lars Christensen; Thorshavn ekspedisjoner; geografi; hvalfangere; hvalfangst; oppdagelsesreiser

Antarctic Circumnavigation by the "Norvegia" (Geographical Review, 1931)
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjonen; ekspedisjoner; forskning; geografi; polarområdene

Norvegia-ekspedisjonen 1930-1931 (Norges geografi oppmåling, 1931)
Keywords: Antarktis; Bouvetøya; Norvegia ekspedisjoner; Sørishavet; geografi; kartlegging

Sydishavet - Kong Haakon VII hav (Norges geografi oppmåling, 1931)
Keywords: Antarktis; Sørishavet; ekspedisjoner; geografi; kartlegging

Antarctic Research by the Norvegia Expeditions and Others - Holtedahl, Olaf (The Geographical Journal, 1931)
Keywords: Lars Christensen; Norvegia ekspedisjonene; Odd I.; Sørishavet; ekspedisjonen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

I. Norske undersøkelser ved Sydpollandet 1929-1931. II. Norvegia-ekspedisjonen 1930-1931 : omseilingen av Sydpollandet - Isachsen, Gunnar (1931)
Keywords: Antarktis; Hjalmar Riiser; Lars Christensen; Larsen; Norvegia ekspedisjonen; Sydpolen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; meteorologi; oppdagelsesreiser; oseanografi

Den Tredje »Norvegia«-Ekspedisjon 1929—1930 - Riiser-Larsen, Hjalmar (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1930)
Keywords: Bouvetøya; Hjalmar Riiser; Larsen; Norvegia ekspedisjonen; geografi; kartlegging

Mot ukjent land : Norvegia-ekspedisjonen 1929-1930 - Riiser-Larsen, Hjalmar (Gyldendal, 1930)
Keywords: Antarktis; Hjalmar Riiser; Lars Christensen; Larsen; Norvegia ekspedisjonen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; lutfart; oppdagelsesreiser

The "Norvegia" Antarctic Expedition of 1929-1930 - Riiser-Larsen, Hjalmar (Geographical Review, 1930)
Keywords: Antarktis; Hjalmar Riiser; Lars Christensen; Larsen; Norvegia ekspedisjonen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; lutfart; oppdagelsesreiser

Antarctic whaling and exploration - Aagaard, Bjarne (Scottish Geographical Magazine, 1929)
Keywords: Lars Christensen; Norvegia ekspedisjonene; Sørishavet; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

[Kart over Antarktika og Sydishavet]. Skisser med "Odd" og "Norvegia" sine ruter i Antarktis 1927-1929 - [Aagaard, Bjarne] (1929)
Keywords: Antarktis; Norvegia ekspedisjoner; Odd I; Sørishavet; ekspedisjonen; geografi; kartlegging

Peter I Øy - Larsen, Nils (1929)
Keywords: Lars Christensen; Norvegia ekspedisjonen; Peter I. Øy; geografi; kartlegging

Die norwegische Bouvetinsel - Sachse, Walter (Dr. A. Petermann's Mitteilungen aus Justus Perthes' Geographischer Anstalt, 1929)
Keywords: Bouvetøya; Norvegia ekspedisjoner; geografi; oppdagelsesreiser

Die norwegische Peter-I.-Insel - Sachse, Walter (Dr. A. Petermann's Mitteilungen aus Justus Perthes' Geographischer Anstalt, 1929)
Keywords: Odd I; Peter I. Øy; ekspedisjonen; geografi; oppdagelsesreiser

The "Norvegia"-expedition and Bouvet Island - Aagaard, Bjarne (Norges Handels og Sjøfartstidende, 1928)
Keywords: Antarktis; Bouvetøya; Lars Christensen; Norvegia ekspedisjonen; ekspedisjoner; geografi; historie; internasjonal; politikk; rett

James Cook - Haffner, Einar (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1928)
Det er i år 150 år siden James Cook døde. Der er så mange jubileer og minnefester i våre dager at man undertiden synes det kan bli litt for meget av det gode. Men de efterfølgende minneord er helliget en mann som ingen der er geografisk interessert, nogensinde bør glemme.
Keywords: James Cook; Sørishavet; geografi; oppdagelsesreiser; polarekspedisjoner; polarfarere

Fra det norske forskningsarbeide i de vest-antarktiske strøk syd-sommeren 1927—28 - Holtedahl, Olaf (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1928)
Keywords: Lars Christensen; Odd I; Peter I. Øy; ekspedisjonen; geografi; kartlegging

The Norwegian South Polar Expedition - Amundsen, Roald (The Geographical Journal, 1913)
Keywords: Antarktis; Fram (skip); Sydpolsekspedisjonen; ekspedisjoner; geografi; oppdagelsesreiser; polarområdene

Amundsen`s Attainment of the South Pole (The National geographic magazine, 1912)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Amundsen's Expedition to the South Pole (Bulletin of the American Geographical Society, 1912)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Sydpolen: den norske sydpolsfærd med Fram 1910-1912 - Amundsen, Roald (Jacob Dybwads forl., 1912)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Sydpolen: den norske sydpolsfærd med Fram 1910-1912 - Amundsen, Roald (Jacob Dybwads forl., 1912)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

The South Pole : an account of the Norwegian Antarctic expedition in the "Fram" 1910-1912 - Amundsen, Roald (Murray, 1912)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

The South Pole : an account of the Norwegian Antarctic expedition in the "Fram" 1910-1912 - Amundsen, Roald (Murray, 1912)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Amundsen`s Antarctic Explorations - Brown, R N Rudmose (Scottish Geographical Magazine, 1912)
Keywords: Antarktis; Fram (skip); ekspedisjoner; geografi; oppdagelsesreiser; polarområdene; sydpolen

Nærmest Sydpolen : Aaret 1900 - Borchgrevink, Carsten Egeberg (Gyldendal, 1905)
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; biografier; botanikk; ekspedisjonen; ekspedisjoner; forskning; første landgang; geografi; geologi; oppdagelsesreiser; overvintring; polarekspedisjoner; zoologi

The "Southern Cross" Expedition to the Antarctic, 1899-1900 - Borchgrevink, Carsten Egeberg (The Geographical Journal, 1900)
Keywords: Antarktis; Southern Cross; biologi; ekspedisjonen; ekspedisjoner; forskning; geografi; meteorologi; oppdagelsesreiser; overvintring; zoologi